Acute liver failure in Turkey: A systematic review - Cüneyt Kayaalp; Veysel Ersan; Sezai Yılmaz (Turkish Journal of Gastroenterology, 2019)
Background/Aims: To present the causes of acute liver failure in Turkey. Materials and Methods: International and national medical research databanks were searched for publications related to acute liver failure and originating from Turkey. Patients in the databank of acute liver failure of our center were also added to this literature search. Patients were evaluated for age, gender, etiology, treatment modality, and outcomes. Results: A total of 308 patients were analyzed. Hepatitis A (20.9%) for children and hepatitis B (34.7%) for adults were the most common causes of acute liver failure. Cryptogenic (18%) and metabolic (14%) reasons were the followings. Wilson’s disease was the most common cause of metabolic diseases. Mushroom intoxication was the most frequent factor of toxic liver failure for both adults and children (13%). Firework intoxication, including yellow phosphorus, is an indigenous factor. Anti-tuberculosis agents (3.2%) were the main cause of drug-induced acute liver failures (9%). Paracetamol was responsible for only 0.7% of all acute liver failures. Survival of the transplanted patients (n=118) was better than the non-transplanted patients (n=178) (65% vs. 36% respectively, p<0.001) Conclusion: Preventable causes of acute liver failure in Turkey include hepatitis viruses and intoxication. Active vaccination and public awareness can decrease the number of acute liver failures. Paracetamol is not an emerging reason for acute liver failure in Turkey now, but selling it over the counter may increase the risks. Turkish Başlık: Türkiye’de akut karaciğer yetmezliği: sistematik derleme Anahtar kelimeler: Akut karaciğer yetmezliği, hepatit virusları, transplantasyon, sistematik derleme, epidemiyoloji Arkaplan/Amaç: Türkiye’de akut karaciğer yetmezliği nedenlerini ortaya koymak. Yöntemler ve Gereçler: Ulusal ve uluslararası veri bankalarından Türkiye kaynaklı akut karaciğer yetmezliği ile ilgili çalışmalar araştırıldı. Ayrıca kendi merkezimizdeki olgular oluşturulan veri bankasına eklendi. Hastalar yaş, cinsiyet, etioloji, tedavi şekli ve sonucu açısından değerlendirildi. Bulgular: Toplam 308 hasta değerlendirildi. Çocuklarda hepatit A (%20.9), erişkinlerde ise hepatit B virusları (%34.7) en sık akut karaciğer yetmezliği nedenleriydi. Kriptojenik (%18) ve metabolik nedenler (%14) onları takip ediyordu. Wilson hastalığı en sık akut karaciğer yetmezliğine neden olan metabolik hastalıktı. İntoksikasyonlar (%13) arasında mantar zehirlenmesi hem erişkinlerde hem de çocuklarda en önemli nedendi. Çat-pat zehirlenmesine bağlı akut karaciğer yetmezliği ülkemize özgü nedenlerdendi. İlaca bağlı nedenler (%9) içinde anti-tuberküloz ilaçlar en sık (%3.2) etken olmasına karşın parasetamol tüm akut karaciğer yetmezliklerinin ancak %0,7’sinden sorumluydu. Karaciğer nakli imkanı bulabilen hastalarda (n=118) yaşam süresi bu imkanı bulamayan hastalara (n=178) göre daha iyi bulundu (%65’ e karşın %36, p<0.001). Sonuç: Türkiye’de akut karaciğer yetmezliğinin korunulabilir nedenlerini hepatit virusları ve zehirlenmeler oluşturmaktadır. Aktif aşılama programları ve halkın bilgilendirilmesi akut karaciğer yetmezliklerinin sayısını azaltabilir. Parasetamol günümüzde Türkiye için çok önemli bir akut karaciğer yetmezliği değildir ancak reçetesiz satılması riskleri arttırabilir. <span style="color: black; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;">